Process innovation in small firms case studies on CNC machine tools - Vonortas, Nicholas S. (Technovation)
This paper reports the results of a study on the implementation of process innovations, and the benefits thereof, in a sample of small metalworking firms in a mid-Atlantic region of the US. No firm experienced serious organizational or technical problems in making substantial investments in CNC technologies and implementing them effectively. One reason for this discrepancy may be that the firms that were interviewed have had prior experience with CNC. The most compelling reason for introducing process innovations was the pressure exerted by large sophisticated customers with whom the interviewed firms have had long-term relationships. The implication is that government policies aiming at assisting small manufacturers to modernize should not overlook the strong 'pull' effect of the markets targeted by these manufacturers.